Personal fable dan Sensation seeking pada Remaja Awal Pengendara Motor - Sodil, A. Nurfardhia Gita Yani; Daud, M.; Fakhri, Nurfitriany (SOCIETIES: Journal of Social Sciences and Humanities, 2024)
Abstract. Early adolescents often engage in dangerous behavior, which is a form of sensation-seeking behavior and can be classified as a form of personal fable because it is done intentionally and can endanger others. This study aimed to determine the relationship between personal fables and sensation-seeking in the early teens of motorcyclists in Makassar. The subjects in this study were 408 boys who were early teenagers. The sampling technique in this study is cluster sampling using quantitative methods. Measuring instruments used in this research are sensation seeking scale and personal fable scale. Analyzed using Product moment correlation analysis techniques with the help of SPSS 23.0 for Windows. The results showed a positive relationship between personal fable and sensation seeking in early adolescents (p = 0,000, r = 0.401). This study illustrates that the higher the level of personal fable, the higher the sensation seeking of early teenage motorcyclists in the city of Makassar. The results of this study are expected to reduce the level of motorcyclists in early adolescents, given that early teenagers have not been able to control their cognition. Keywords: Early Teenager, motorcyclists, personal fable, sensation-seeking